New records of hover flies (Diptera, Syrphidae) from Ukraine. IV - Prokhorov, A. V.; Popov, G. V.; Shparyk, V. Yu. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2020)
Six additional species of hover flies of the subfamily Eristalinae are recorded fromUkraine for the first time: Criorhina pachymera Egger, 1858, Hammerschmidtia ferruginea (Fallén, 1817),Melanogaster parumplicata (Loew, 1840), Orthonevra erythrogona (Malm, 1863), Sphiximorpha garibaldiiRondani, 1860, and Temnostoma angustistriatum Krivosheina, 2002. Distributions of these species aresummarized and species diagnoses are provided. Updated key to males of the European species of thegenus Melanogaster including a little-known M. jaroslavensis (Stackelberg, 1922) is proposed.